A Meta-Analysis of High-Intensity Interval Training on Glycolipid Metabolism in Children With Metabolic Disorders - Cao, Meng; Li, Shu; Tang, Yucheng; Zou, Yu (Frontiers in Pediatrics, 2022)
Objective Metabolic disorders are common among children and adolescents with obesity and are associated with insulin resistance, hyperlipidemia, hypertension, and other cardiovascular risk factors. High-intensity interval training (HIIT) is a time-efficient method to improve cardiometabolic health. We performed a meta-analysis to determine the effects of HIIT on glycolipid metabolism in children with metabolic disorders. Methods Meta-analyses were conducted to determine the effect of HIIT on glycolipid metabolism markers. Subgroup analysis with potential moderators was explored (i.e., training intensity standard and work/rest time ratio). Results Eighteen trials involving 538 participants were included. HIIT showed positive effects on glycolipid metabolism, such as TG, TC, LDL-C, HDL-C, BG, BI, and HOMA-IR when compared to the non-training control group (CON), in addition to BG (p = 0.257), the combined results of other indicators have high heterogeneity (p = 0.000). HIIT showed no superior effects when compared to moderate-intensity training (MIT). Subgroup analysis demonstrated HIIT protocol with work/rest time ratio of 1:1 was superior to MIT for reducing TG and LDL-C, used %MAS as the exercise intensity was superior to MIT for reducing TG. HIIT protocol used %HR as the exercise intensity was superior to MIT for increasing HDL-C, decreasing BI, and HOMA-IR. Conclusion HIIT improved glycolipid metabolism in children with metabolic disorders. Work/rest time ratio and training intensity can affect the intervention effects of HIIT.